Aorta Artery and Branches in Tucanuçu (Ramphastostoco – Muller, 1776) - Filho, Fábio Carlos da Silva; Barros, Roseâmely Angélica de Carvalho; Oliveira, Thalles Anthony Duarte; Oliveira, Tarley Santos; Oliveira, Lanussy Porfiro de; Nunes, Bruna Rafaella de Almeida; Mesquita, Diogo Baldin; Oliveira, Thiago Sardinha de; Silva, Zenon (International Journal of Environment, Agriculture and Biotechnology, 2019)
Tucanuçu (Ramphastostoco – Muller, 1776) is the largest Tucano birds and possess remarkable characteristics, such long orange beak and black spot on end, its black plumage, an area of bare orange skin around the eyes and blue eyelids, being a symbol of avian diversity found in South American ecosystems, whose anatomy and systemic description are little studied, fundamental process to understand biological system of this animal. Thus, this work aimed to perform an anatomical description of aorta artery and respective branches in Tucanuçu through a comparative study, using 2 male and 2 female specimens. In this sense, the present work shows unprecedentedly discovered about this animal that vascular pattern shows similarities with other birds and Aorta being the main vessel that emerges from left ventricle base of the heart. The first branches of Aorta are three coronary arteries: Right, Left and Dorsal. Brachiocephalic Aa.andCervicobrachialarises from cranial face of aortic arch and directed: Brachiocephalic a. which is left limbs, to head, neck and left thoracic member and Cervicobrachial to neck and right thoracic limb.